Effectiveness of Rectification in Audit Sampling. - Wurst, John; Neter, John; Godfrey, James (The Accounting Review, 1991)
This article considers audit sampling and the auditor's risks of incorrect conclusions in deciding whether an accounting population contains a material error amount. The proposed new sample evaluation procedure takes into account the correction of all errors observed in the sample and calculates a modified upper bound on the total error amount remaining in the unsampled population. This procedure is known as rectification. It is shown that rectification significantly reduces the risk of incorrect rejection when sample sizes of 150 and 300 are used. Since the size of the error amount observed in the sample is crucial to the extent of risk reduction, the first stage of this study investigated the magnitude of rectification for three dollar-unit sample selection methods commonly used in practice-systematic, random, and cell selection. Theoretical results for the expected error amount contained in systematic samples were obtained for 32 different study populations for three sample sizes (65, 150, and 300). Simulation was used to estimate the expected error amounts with random and cell selection for the same 32 study populations and three sample sizes. The results show that the average error amount subject to rectification with cell selection is very close to that with systematic selection for alt three sample sizes. Random selection produced smaller expected error amounts than did systematic selection, especially for the larger sample sizes. In the second part of the study, the risks of incorrect rejection with and without rectification were compared. Factors considered in this comparison were sample size (65, 150, or 300) and sampling method (systematic, random, or cell). Use of rectification led to noticeable reductions in the risk of incorrect rejection for sample sizes other than 65. For a given application, auditors will need to determine whether the cost of the additional sampling is balanced by the savings from the reductions in the risk of incorrect rejection with rectification.